Experimental modifications imply a stimulatory function for male tsetse fly genitalia, supporting cryptic female choice theory - Eberhard Chabtree, William G. (2009)
One of the most sweeping of all patterns in morphological evolution is that animal genitalia tend to diverge more rapidly than do other structures. Abundant indirect evidence supports the cryptic female choice (CFC) explanation of this pattern, which supposes that male genitalia often function to court females during copulation; but direct experimental demonstrations of a stimulatory function have been lacking. In this study, we altered the form of two male genital structures that squeeze the female's abdomen rhythmically in Glossina pallidipes flies. As predicted by theory, this induced CFC against the male: ovulation and sperm storage decreased, while female remating increased. Further experiments showed that these effects were due to changes in tactile stimuli received by the female from the male's altered genitalia, and were not due to other possible changes in the males due to alteration of their genital form. Stimulation from male genital structures also induces females to permit copulation to occur. Together with previous studies of tsetse reproductive physiology, these data constitute the most complete experimental confirmation that sexual selection (probably by CFC) acts on the stimulatory properties of male genitalia.